Analisis Akuntabilitas dan Transparansi dalam Pengelolaan Bantuan Langsung Tunai (BLT) Tahun 2021 di Desa Kota Raja, Kabupaten Tanjung Jabung Timur - Andi Uliyanti; Ratih Kusumastuti; Muhammad Ridwan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to determine the accountability and transparency in the management of Direct Cash Assistance (BLT) in Kota Raja Village, Tanjung Jabung Timur Regency. This study was conducted using a qualitative descriptive method. The types of data used are primary data and secondary data. The data collection techniques used were questionnaires and observations. The population in this study was The population in this study were 40 village government officials, namely the Village Head, Village Secretary, Planning Head, Finance Head, RT Head, Hamlet Head and BPD members consisting of the BPD Chair, BPD Deputy Chair, BPD Secretary, Several BLT Recipient Communities in Kotar Raja Village. The data analysis method used in this study is a quantitative descriptive method. The results of this study indicate that the management of Direct Cash Assistance (BLT) in Kotar Raja Village has implemented the principles of Accountability and Transparency.